Determinants of the use of contraceptive methods by adolescents in the Democratic Republic of the Congo: results of a cross-sectional survey - Dieudonné M. Mpunga; Faustin M. Chenge; Thérèse NM. Mambu; Pierre Z. Akilimali; Mala A. Mapatano; Gilbert U. Wembodinga (BMC, 2022)
Plain English summary The use of contraceptive methods remains low among adolescents aged 15 to 19 in the Democratic Republic of the Congo. However, family planning (FP) methods can help to prevent unintended pregnancies. This study aimed at identifying the socio-demographic factors that prevent teenage girls from using FP methods. We analyzed the data from the Performance, Monitoring and Accountability project (PMA 2020), seventh round, collected in Kinshasa and Kongo Central provinces. The use of contraceptive methods by sexually active adolescents was measured according to the level of education, age, province, religion, marital status, number of children, knowledge of contraceptive methods and household income. For the 943 adolescent girls interviewed, the use of any contraceptive method was calculated at 22.6, 18.1 and 19.9%, respectively in Kinshasa, Kongo Central and overall. The use of traditional methods was estimated at 8.0% overall, higher in Kinshasa (12.7%) and lower (4.7%) in Kongo Central. However, the use of modern contraceptive methods was estimated at 9.9, 13.4 and 12.0% respectively in Kinshasa, Kongo Central and overall. Poor knowledge of contraceptive methods; low-income and living in Kongo central province were the factors associated with the low use of any contraceptive method. In conclusion, the progress in the use of contraceptive methods by adolescent girls is not yet sufficient, due to some socio-demographic barriers. These results suggest to fight against such factors; and to make contraceptive services available, accessible, and affordable for teenagers.